Transformation of Catur Guru Educated in Preventing Cases of Cyber Sexual Harassment Among Adolescents in Bali Province - I Gusti Agung Alit Suryawati (Persatuan Wartawan Indonesia, 2022)
Among the problems of teenagers in today's digital technology era is sexual violence through social media which is more targeted at youth groups. This research report discusses: (1) What are the forms of sexual violence through social media that kill teenagers? (2) How is the transformation of the Catur Guru teaching in preventing sexual violence against teenagers? As a result of qualitative research, research data were obtained through document study, observation, and in-depth interviews with students or youth, educators, and stakeholders related to the problems studied. The data collected was analyzed by descriptive qualitatively and applying the theory of symbolic interactionism and the theory of developmental ecology. The results of the study show that first, the form of sexual violence that is spread by social media to adolescents is the dissemination of content in the form of photos and videos by students that leads to violence in the form of threats and the real of pornography, so, based on the case of sexual violence, education is needed. in the form of understanding to be wiser in using media and assistance to students or teenagers in using social media. Second, the sexual violence experienced by teenagers can be anticipated by implementing the Catur Guru teachings, namely: (a) maintaining religious awareness (Guru Swadyaya) so that teenagers do not fall into sexual behavior that violates religious norms, (b) parental assistance for teenagers (Guru Rupaka), which is adequate, (c) there is a sufficient direction and sexual education by teachers at the school (Guru Pengajian) which is quite intensive so that teenagers do not become victims of sexual violence, and (d) the implementation of strict policies by the government (Guru Wisesa) in brake the negative influence of social media. Socialization of Catur Guru teachings in curbing the negative influence of social media through outreach activities about the dangers of sexual violence and legal action for violators. The socialization of Catur Guru teachings in anticipating sexual violence against teenagers from social media needs to be developed. In addition, strict legal action must be put in place so that violators of sexual violence can be anticipated.